MOA between UiTM and UMS - Khong, Heng Yen (Universiti Teknologi MARA, Sarawak, 2017)
Universiti Teknologi MARA (UiTM) Malaysia and Universitas Muhammadiyah Surakarta (UMS), Indonesia signed Memorandum of Agreement (MoA) at Siti Walidah Building, UMS campus, Pabelan Kartasura, Sukoharjo on 2 February 2017. The signing was represented by the Rector, UiTM Sarawak, Professor Dato Dr. Jamil Haji Hamali and UMS Rector, Professor Dr. Bambang Setiaji. The MoA outlined the research activities on the evaluation of pharmacological activities such as anti-diabetic, anti-hyperuricemia, anti-hypercholesterol, antioxidant and cytotoxic activities as well as the phytochemical studies on the potential natural sources in innovative herbal product development. The research team leaders consist of Associate Professor Dr. Khong Heng Yen from UiTM as well as Associate Professor Dr. Haryoto and Associate Professor Dr. Muhtadi from UMS.